Africa and the Olympic Movement: challenges, strategies and influences of France in the internationalization of African sport (1944-1966) - (:unkn) unknown (My University, 2010)
The goal of the thesis is to study the role and influence of France in the process of internationalising sport in French-speaking sub-Saharan Africa in the framework of the Olympic Movement (1944-1966). It aims to show how competitive sporting events between France and Africa during the colonial period and then at decolonisation revealed the dynamic of the changes in the political systems governing African sport (national and international federations, NOC). In the post-war contex...
Keywords: African Research